Graphomania as daily practice (based on andrei Bolotov’s archive and memoirs) - Веселова, Александра (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
Andrei Bolotov (1738–1833) was one of the most prolific writers of the 18th and early 19th centuries, although much of his heritage remained unpublished. In the subsequent critical and scholarly literature the assessments of his works vary from enthusiastic to derogatory. But the reputation of a graphomaniac, one that stuck with Bolotov, is largely due to the difference in the perception of a literary work in the 18th and the subsequent centuries. On basis of Bolotov’s memoirs, as well as a number of archival sources, now first made available for scholarly enquiry, the article analyses Bolotov’s reflection on the writing process itself and his attitude to his own works, not only as fruits of his creativity, but also as material objects. Such an attitude is characteristic of his epoch and rooted in the earlier tradition of Old Russian booklore.